Analisis Nilai Tambah Dan Kelayakan Usaha Penggilingan Padi Di Kecamatan Buay Bahuga, Kabupaten Way Kanan, Lampung - Ary Eko Prastya Putra (Jurnal Bakti Agribisnis, 2017)
The objectives of this research are: 1) To know the production cost and income of paddy mill business in Buay Bahuga Sub-district of Way Kanan Regency, 2) To know the value added of rice mill business in Buay Bahuga Sub-district of Way Kanan Regency, 3) To know the feasibility of rice milling business in the District of Buay Bahuga District Way Kanan. The results showed that the total production of rice milling business that is equal to 75.096 kg / year with the selling price of Rp 7,700 / kg, the revenue of Rp 578,239,200 is obtained, the use of production cost of Rp 800.006.105, the income of Rp -221.766.905 . Added value to the paddy mill business in Buay Bahuga District is Rp 578,239,200. with the use of the intermediate fee of Rp 382,505,680. The rice milling business in Kecamatan Buay is also feasible to be developed financially.